Decentralizing Identity with Blockchain Technology in Digital Identity Management - Kumar, Aayush (Journal of Current Research in Blockchain, 2024)
Blockchain technology has emerged as a promising solution for digital identity verification, offering significant improvements in security, decentralization, and privacy. This study examines the application of blockchain in identity systems, focusing on the benefits and challenges it presents. The findings reveal that blockchain enhances security by 85%, decentralizes data control by 80%, and improves privacy protection by 75% compared to traditional centralized systems. Additionally, the study highlights key challenges, including regulatory uncertainty, scalability issues, and interoperability concerns. Regulatory gaps remain a major obstacle to widespread adoption, despite a rapid increase in blockchain adoption rates from 5% in 2016 to 75% in 2022. Scalability also poses significant technical challenges, with public blockchains struggling to handle large transaction volumes efficiently. Through a comparative analysis, the study shows that blockchain-based identity systems outperform traditional centralized systems in terms of data control (90% vs. 40%), security (85% vs. 50%), and transparency (95% vs. 30%). However, traditional systems still lead in scalability by 10%. This paper concludes that while blockchain holds the potential to revolutionize identity verification, addressing regulatory, scalability, and interoperability issues is critical to achieving its full potential. Future research should focus on developing more scalable consensus mechanisms and standardized frameworks to promote adoption, ensuring blockchain’s viability as a global identity management solution.